Semantic web and decision support systems - Antunes, Francisco (2018)
Semantic Web technologies are intertwined with the decision-making process. In this paper the general objectives of the semantic web tools are reviewed and characterized, as well as the categories of decision support tools, in order to establish an intersection of utility and use. We also elaborate on actual and foreseen possibilities for a deeper integration, considering the actual implementation, opportunities and constraints within the context of decision-making. We conclude that a broader or generalized Semantic Web integration in the decision support community is still a work in progress and much remains to be done.